RELATIONSHIP ANALYSIS OF SHRINKAGE LEVEL, MOISTURE CONTENT, AND DRYING RATE OF EUCHEUMA COTTONII SEAWEED IN VARIOUS DRYING TIME AND METHODS - Lestari, Mega Fia; Aras, Neny Rasnyanti M (Indonesian Journal of Fundamental Sciences, 2024)
In this study, shrinkage level, moisture content, and drying rate of Eucheuma cottonii seaweed were compared using various drying times and methods. Both sun and wind drying were employed, with drying times ranging from 0 to 240; 480; 720; and 960 minutes for each method. In Pajukukang Subdistrict, Bantaeng Regency, Eucheuma cottonii seaweed was harvested and dried using a variety of drying methods. The findings indicated that the Pajukukang Subdistrict was extremely hot, with the greatest temperatures and relative humidity readings of 52.4 oC and 47% RH (sun drying) and 32.6 oC and 55% RH (wind drying). The seaweed also changed after drying, going from a fresh brown color to a deeper brown color with an extremely dry physical shape (sun drying) and dry with white spots all over its surface (wind drying). Additionally, when drying time increases, shrinkage level increases. On a wet and dry basis, however, the converse occurred, where the two types of moisture content dropped as the drying time increased. When the drying time increases for both drying processes, a phenomena known as a falling rate period happens for the relationship between the drying rate and the moisture content on a dry basis.